Te-CANFIELDITE FROM THE LUNNOE Au-U DEPOSIT (ALDAN REGION, REPUBLIC OF YAKUTIYA) - K.А. Novoselov; E.V. Belogub; I.A. Blinov (Минералогия)
Te-canfieldite was found in assemblage with pyrite, marcasite, hessite, and Tl sulfosalts in the ores of the Fedorovskaya vein zone of the Lunnoe Au-U deposit, Aldan shield (Yakutia). The mineral forms anhedral inclusions in vein matrix. Its reflection spectrum is characterized by weak normal dispersion, the dispersion curve is almost parallel to the canfieldite curve, but the reflectivity value is significantly higher. A sustained S:Te ratio of Te-canfildite is consistent with the analytical data for most mineral localities (Lengenbach, Sirotan, Nikolayevskoye, Uryakh). It is suggested that Te-canfieldite is formed in a wide range of geological settings.